Nanostructuring of Additively Manufactured 316L Stainless Steel via High-Pressure Torsion for Enhanced Strength and Corrosion Performance - Mohd Yusuf, Shahir; Gao, Nong (International Journal of Integrated Engineering, 2024)
Bulk nanostructured materials (BNM) are defined as metallic materials with grain sizes